Assimilation Performance of Blue Lupine Depending on the Elements of Cultivation Technology in Conditions of Ukrainian Polissia - Ратошнюк, В. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The purpose of this article is to study of characteristics of leaf surface formation by plants of blue lupine; accumulation of dry substance; determination of net planting productivity of photosynthesis depending on variety; fertilizer; sowing method; seeding rate and the conditions of mineral nutrition; taking into account the effect of foliar application in different phases of culture development. Optimization of the conditions of mineral nutrition by mineral fertilizers in N30-60Р60К60 norm in combination with two foliar feedings by water-soluble nitrogen-phosphorus-potassium fertilizers with microelements provides the formation of the largest indicators of leaf area; photosynthetic potential and photosynthetic plant productivity of blue lupine; which in its turn creates the preconditions of its maximum productivity.